Primary pigmented nodular adrenocortical disease - Ngow, Harris Abdullah; Khairina, Wan Mohd Nowalid Wan (The Polish Society of Endocrinology, 2011)
Primary pigmented nodular adrenocortical disease (PPNAD) is a rare adrenal tumour causing corticotrophin-independent Cushing's syndrome. It occurs mainly in children and young adults. The histological examination is characterised by small pigmented micronodules on the adrenal cortex. The diagnosis is most often seen in patients with Carney Complex, but it can also occur in isolation. We report a case of Carney Complex that was referred for adrenalectomy. The procedure was uneventful and the patient was well at discharge. The adrenal pathology showed numerous black nodules measuring less than 2mm in diameter. This feature was pathognomonic of primary pigmented nodular adrenocortical disease.